الوحدة النفسية لدى المرأة غير المنجبة (دراسة ميدانية في محافظة اللاذقية) - شريف, ليلى; كحيلة, ريم; خاسكة, سمر (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
هدفت هذه الدراسة إلى تعرّف الوحدة النفسية لدى عينة من النساء غير المنجبات في محافظة اللاذقية في الجمهورية العربية السورية وتعرف الفروق بين أفراد عينة البحث تبعاً لمتغيرات الدراسة: الإقامة ( ريف, مدينة ) , عدد سنوات الزواج (أقل من عشر سنوات , عشر سنوات فأكثر ) , العمل ( عاملة, غير عاملة ) , المستوى التعليمي ( محو أمية , إعدادي , ثانوي, جامعي, أكثر من جامعي ) و قد اعتمدت الدراسة المنهج الوصفي , واتخذت الباحثة من الاستبانة أداةً رئيسة لأخذ آراء أفراد عيّنة الدراسة وتمثلت الاستبانة بمقياس الوحدة النفسية وتم تطبيقها على عينة مؤلفة من (47) امرأة تم اختيارهن بطريقة عشوائية . النتائج : - وجدت الوحدة النفسية بنسبة متوسطة عند أفراد عينة البحث من النساء غير المنجبات .- لا توجد فروق دالة إحصائياً عند مستوى دلالة (0.05) لدى أفراد عينة البحث من النساء غير المنجبات في محافظة اللاذقية على مقياس الوحدة النفسية وفق متغير عدد سنوات الزواج (أقل من عشر سنوات , عشر سنوات فأكثر ).- توجد فروق دالة إحصائياً عند مستوى دلالة (0.05) لدى أفراد عينة البحث من النساء غير المنجبات في محافظة اللاذقية على مقياس الوحدة النفسية وفق متغير العمل (عاملة، غير عاملة).- توجد فروق دالة إحصائياً عند مستوى دلالة (0.05) لدى أفراد عينة البحث من النساء غير المنجبات في محافظة اللاذقية على مقياس الوحدة النفسية وفق متغير مكان الإقامة (مدينة، ريف).- لا توجد فروق دالة إحصائياً عند مستوى دلالة (0.05) لدى أفراد عينة البحث من النساء غير المنجبات في محافظة اللاذقية على مقياس الوحدة النفسية وفق متغير المستوى التعليمي (محو أمية، إعدادي, ثانوي, جامعي, أكثر من جامعي).This study aimed to know the Psychological Loneliness in a sample of infertility women in Lattakia in Syrian Arab Republic and to known differences between sample search on the variables of the study: Residence (rural, city), work (working, non-working), the education level (illiteracy erasure , preparatory , secondary , academic , higher of academic) . the study has been adopted the descriptive , method the researcher has taken the scale method as a main tool to take the opinions of the members the questionnaire has been accomplished by the Loneliness scale and it was applied on a sample consisting of 47 women were selected randomly. Results: found by Moderately among a sample search of infertile women. The Loneliness- - There are no differences have statistical indication on at the level of significance (0.05)among a sample search of infertile women in Lattakiah members of the on a scale the Psychological Loneliness according to marriage years number variable.( Less than ten years,Ten years and over). - There are no differences have statistical indication on at the level of significance (0.05)among a sample search of infertile women in the province of Lattakiah members on a scale the Psychological Loneliness according to work variable (does not work, work). - There are differences have statistical indication on at the level of significance (0.05) among a sample search of infertile women in the province of Lattakiah on a scale the Psychological Loneliness according to variable place of residence(city , rural) - There are no differences have statistical indication on at the level of significance (0.05) among a sample search of infertile women in the province of Lattakiah on a scale the Psychological Loneliness according to the education level variable (illiteracy erasure , preparatory , secondary , academic , higher of academic).